+0  
 
0
217
1
avatar

sin2x-sqrt(3)*cosx=o

Guest Apr 18, 2017
 #1
avatar
0

Solve for x:
sin(2 x) - sqrt(3) cos(x) = 0

Expand trigonometric functions:
2 cos(x) sin(x) - sqrt(3) cos(x) = 0

Collecting terms, 2 cos(x) sin(x) - sqrt(3) cos(x) = (2 sin(x) - sqrt(3)) cos(x):
cos(x) (2 sin(x) - sqrt(3)) = 0

Split into two equations:
cos(x) = 0 or 2 sin(x) - sqrt(3) = 0

Take the inverse cosine of both sides:
x = π/2 + π n_1 for n_1 element Z
 or 2 sin(x) - sqrt(3) = 0

Add sqrt(3) to both sides:
x = π/2 + π n_1 for n_1 element Z
 or 2 sin(x) = sqrt(3)

Divide both sides by 2:
x = π/2 + π n_1 for n_1 element Z
 or sin(x) = sqrt(3)/2

Take the inverse sine of both sides:
x = π/2 + π n_1 for n_1 element Z
 or x = π - sin^(-1)(sqrt(3)/2) + 2 π n_2 for n_2 element Z or x = sin^(-1)(sqrt(3)/2) + 2 π n_3 for n_3 element Z

sin(2 x) - sqrt(3) cos(x) ⇒ sin(2 (π/2 + π n_1)) - sqrt(3) cos(π/2 + π n_1) = 0:
So this solution is correct

sin(2 x) - sqrt(3) cos(x) ⇒ sin(2 (329 π - sin^(-1)(sqrt(3)/2))) - sqrt(3) cos(329 π - sin^(-1)(sqrt(3)/2)) = 0:
So this solution is incorrect

sin(2 x) - sqrt(3) cos(x) ⇒ sin(2 (184 π + sin^(-1)(sqrt(3)/2))) - sqrt(3) cos(184 π + sin^(-1)(sqrt(3)/2)) = 0:
So this solution is incorrect

The solution is:
Answer: | x = π/2 + π n_1 for n_1 element Z          or x = π - sin^(-1)(sqrt(3)/2) + 2 π n_2 for n_2 element Z            or x = sin^(-1)(sqrt(3)/2) + 2 π n_3 for n_3 element Z

Guest Apr 18, 2017

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.